Right to health of immigrant minors in Italy and Europe (Italian Journal of Public Health, 2012)
Undermined survival is usually the reason to migrate: wars, persecutions, famines, natural calamities are just few examples, as well as cultural, economic, social or religious issues.The diversity of these reasons thus correlates with the extreme variability of migrants typologies and their origin countries. Nowadays it has been reached a sufficient stability of the phenomenon, also testified by the growing number of family unities in Italy and all over the Europe, and by the birth of several children in the welcoming country.